Analisis Pelaksanaan Stockpile Terpadu dalam Tata Kelola Pertambangan di Kabupaten Lumajang - Adhania, Lhery Swara Oktaf; Indrayani, Ning Mukti; Sulaiman, Sulaiman (Jurnal Ilmiah Global Education, 2024)
Community economy and Local Original Income as part of factors in regional development. One of the utilization of regional potential is natural resources. Lumajang Regency as one of the districts in East Java Province with the existence of Mount Semeru as one of the active volcanoes in Indonesia. Stockpile is a place that is used as a location for stockpiling mining products of IUP owners. Sand stockpiles are spread in almost all areas of Lumajang Regency. Stockpile management is part of the existing sand business license. Stockpile managers must have an IUP either on their own business or in cooperation with the IUP owner. In improving and structuring existing stockpiles in the Lumajang Regency area, the Lumajang Regency Government through Lumajang Regent Regulation number 40 of 2022 concerning Integrated Stockpiles is expected to organize and increase Regional Original Revenue (PAD) in the form of Non-Metal and Rock Mineral Taxes. This study uses a qualitative descriptive approach, with data collection in the form of interviews, observations and collection of existing regulatory documents. The informants of this research are individuals who are directly involved in mining activities or activities, communities around the integrated stockpile, the community of Lempeni Village, Tempeh District, which has a stockpile divided into an integrated stockpile, regional officials in charge of Non-Metal and Rock Mineral Tax and stockpile managementintegrated. The result of this study is that the community's economy for mining management at integrated stockpile locations increases with the growth of non-formal professions of the surrounding community, namely ticket guards, cleaners, stalls, as joggers, security officers and traffic. Meanwhile, in the people of Lempeni Village, Tempeh District, before there was an integrated stockpile, there was a reduced stockpile and even no longer worked in the mining sector, namely some did not work and some worked as factory workers.